APHRODISIAC EFFECT OF ETHANOLIC EXTRACT OF MUCUNA PRURIENS SEED IN MALE ALBINO MICE (Journal of Biomedical Investigation, 2015)
The seed of Mucuna Pruriens Linn, belonging to the leguminous family (Papilionaceous) has been used in Ayurvedic medicine since ancient times for treatment of male sexual disorder. This study was aimed at evaluating the aphrodisiac effect of the ethanolic extract of Mucuna Pruriens seed in normal male albino mice by looking at the general mating behaviour, libido and potency using sildenafil citrate as the standard reference drug and also to investigate the possible mechanism by which the drug enhances sexual function. Animals were divided into five groups. The first group was used as control (received distilled water) and experimental groups 2 - 5 were divided on the basis of the dosage of extract to the animals as follows: 150mgrkg body weight (group 2), 200mg/kg body weight (group 3) and 250mg/kg body weight as standard. Animals were fed per oral (PO) with distilled water or extract or standard once a day for 7days. Female mice with oestrus phase were used for mating behaviour. The acute toxicity test done showed that Mucuna Pruriens seed has LD,, > 2000mg/kg. The extract administered significantly (P